2018
DOI: 10.1051/e3sconf/20183704005
|View full text |Cite
|
Sign up to set email alerts
|

Flood risk management in the Souss watershed

Abstract: Flooding is the most devasting natural hazards that causes more damage throughout the world. In 2016, for the fourth year in a row, it was the most costly natural disaster, in terms of global economic losses: $ 62 billion, according to a Benfield’s 2016 annual report on climate and natural disasters [1]. The semi-arid to arid Souss watershed is vulnerable to floods, whose the intensity is becoming increasingly alarming and this area does not escape to the effects of this extreme event.. Indeed, the susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Wang assessed the risk of agricultural flooding and waterlogging disasters in Jilin Province and constructed a rainstorm flood risk assessment index system using four aspects: the harmfulness of disaster-causing factors, the sensitivity of disaster-prone environment, the vulnerability of disaster-affected subjects, and the ability of disaster prevention and reduction; it was also pointed out that extreme precipitation events were the main cause of flood disaster [ 6 ]. Bouaakkaz assessed the flood disaster in Susi Basin and found that population size, land abuse, overdevelopment, and other factors rapidly aggravated the vulnerability and susceptibility of flood disasters in this area [ 7 ]. Lv constructed a comprehensive evaluation index system of urban flood-bearing risk based on the vulnerability of flood-bearing capacity and the vulnerability of disaster prevention and mitigation capacity to study the flood-bearing risk of Zhengzhou and considered that the rapid development of urbanization is the main reason for the increased risk of urban flood and waterlogging disasters [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang assessed the risk of agricultural flooding and waterlogging disasters in Jilin Province and constructed a rainstorm flood risk assessment index system using four aspects: the harmfulness of disaster-causing factors, the sensitivity of disaster-prone environment, the vulnerability of disaster-affected subjects, and the ability of disaster prevention and reduction; it was also pointed out that extreme precipitation events were the main cause of flood disaster [ 6 ]. Bouaakkaz assessed the flood disaster in Susi Basin and found that population size, land abuse, overdevelopment, and other factors rapidly aggravated the vulnerability and susceptibility of flood disasters in this area [ 7 ]. Lv constructed a comprehensive evaluation index system of urban flood-bearing risk based on the vulnerability of flood-bearing capacity and the vulnerability of disaster prevention and mitigation capacity to study the flood-bearing risk of Zhengzhou and considered that the rapid development of urbanization is the main reason for the increased risk of urban flood and waterlogging disasters [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the study area is characterized by the presence of the argan steppes. Due to the climatic aggressiveness andthe high anthropogenic pressure, the High Atlas mountains and the Issen basin as a part of it suffering from water erosion risks, including soil degradation and flooding [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Floods are the natural hazard that affects the greatest number of people worldwide (Bouaakkaz et al, 2018) and which causes the highest global economic losses (Benfield, 2016). In recent decades, exposure to floods has increased dramatically in certain regions (Tanoue et al, 2016), due to an…”
Section: Introductionmentioning
confidence: 99%